2015
DOI: 10.1364/ao.54.003032
|View full text |Cite
|
Sign up to set email alerts
|

Stable dual-wavelength Q-switched Nd:YAG laser using a two-step energy extraction technique

Abstract: The generation of stable dual-wavelength pulses from an actively Q-switched Nd:YAG laser operating at 1064 and 1319 nm was demonstrated. Pulse energies of the dual-wavelength laser were extracted by two temporally separated stimulated-emission processes for a single pumping process, thereby avoiding line competition between the two laser transitions. Total energy of the order of 20 mJ was achieved for the two pulses, and the ratio of the pulse energies of the two lasers could be selected by adjusting the outpu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 24 publications
0
4
0
1
Order By: Relevance
“…Se utilizó el modo de operación Q-switch, lo que permite que la energía por pulso del láser pueda ser variada mediante el tiempo de retraso teniendo pulsos cortos del orden de 4 a 6 ns [20,21]. Un a ventaja de usar el modo de operación Q-switch es que nos permite variar la energía por pulso mediante la variación del tiempo de retraso (delay) [22], este procedimiento fue usado satisfactoriamente por Langrock [23] y West [24]. La Fig.…”
Section: B Irradiación Láserunclassified
“…Se utilizó el modo de operación Q-switch, lo que permite que la energía por pulso del láser pueda ser variada mediante el tiempo de retraso teniendo pulsos cortos del orden de 4 a 6 ns [20,21]. Un a ventaja de usar el modo de operación Q-switch es que nos permite variar la energía por pulso mediante la variación del tiempo de retraso (delay) [22], este procedimiento fue usado satisfactoriamente por Langrock [23] y West [24]. La Fig.…”
Section: B Irradiación Láserunclassified
“…So that the beam quality deteriorates sharply and the output power is limited, even causing the damage to the gain media. With the slab laser media proposed, theoretical and experimental studies have shown that slab structure can greatly increase heat dissipation and effectively reduce thermal effects, thus achieving high power and high beam quality laser output [9][10][11] . Among various slab lasers, partially end-pumped slab lasers are of particular interest.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with the dual-wavelength pulse laser achieved by acoustic-optic or passive Q-switched technology, the dual-wavelength pulse laser obtained by EO Q-switched technology has the virtues of high peak power, high stability and a narrower pulse width. Based on this, EO Q-switched dual-wavelength lasers have wide applications in nonlinear frequency conversion, laser drilling, laser spectroscopy, laser ranging and other fields [1][2][3][4][5]. However, at present, the dual-wavelength pulse lasers obtained by EO Qswitched technology are output at the same time, which greatly limits its applications [6][7][8].…”
Section: Introductionmentioning
confidence: 99%